The competences of the professional of the future, the practices of organizations and ambidexterity: A correlational study with professionals of the companies of the ‘S’ System (Research, Society and Development, 2022)
With the first studies initiated in the 1970s, management by competence has, since then, occupied prominence in the practices used by companies around the world, inserted in the most different environments, contexts and markets. However, it is still an unknown and little explored field, but it presents solid and concrete results for the companies that decided to implement it and that are currently included in the list of the best companies in terms of financial results, ambience and employee engagement. Thus, there is a relationship between the competencies of the future in the light of the World Economic Forum and organizational ambidexterity, with the intention of contributing with possible directions for the implementation of a competency-based management model. 30 workers from the 'S' System companies, equally distributed in two northeastern cities, answered a questionnaire with sociodemographic and professional information, scale of the fifteen competences for the future and the scale of organizational practices of impact on the use of competences. Internal consistency of the scales was observed, with alphas and intraclass correlation greater than 0.70. There was a positive correlation between the 15 professional competences of the future and the Organizational practices impacts on the use of competences and the 15 professional competences of the future correlated with Ambidexterity. By emphasizing a condition for assessing the relationship between competencies and organizational practices, it was noted how important the association between these constructs is, not only in empirical terms, but also in terms of applicability in the work system and productivity.